2018
DOI: 10.3390/v10120714
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Detection of Different Zika Virus Lineages via Molecular Computation in a Point-of-Care Assay

Abstract: We have developed a generalizable “smart molecular diagnostic” capable of accurate point-of-care (POC) detection of variable nucleic acid targets. Our isothermal assay relies on multiplex execution of four loop-mediated isothermal amplification reactions, with primers that are degenerate and redundant, thereby increasing the breadth of targets while reducing the probability of amplification failure. An easy-to-read visual answer is computed directly by a multi-input Boolean OR logic gate (gate output is true i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…Base-pairing to the toehold region is extremely sensitive to mismatches, ensuring specificity, and the programmability of both primers and probes makes possible rapid adaptation to new diseases or new disease variants. We have shown that higher order molecular information processing is also possible, such as integration of signals from multiple amplicons 17 . Overall, the use of sequence-specific probes allow construction of strand exchange computation circuits that act as ‘matter computers’, 58 something that is not generally possible within the context of a PCR reaction (which would of necessity melt the computational devices).…”
Section: Introductionmentioning
confidence: 99%
“…Base-pairing to the toehold region is extremely sensitive to mismatches, ensuring specificity, and the programmability of both primers and probes makes possible rapid adaptation to new diseases or new disease variants. We have shown that higher order molecular information processing is also possible, such as integration of signals from multiple amplicons 17 . Overall, the use of sequence-specific probes allow construction of strand exchange computation circuits that act as ‘matter computers’, 58 something that is not generally possible within the context of a PCR reaction (which would of necessity melt the computational devices).…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we developed a novel multiplex LAMP detection scheme to analyze multiple RNA targets simultaneously. Previous efforts to perform sequence-specific detection of LAMP products have relied on a branch migration-based strand displacement mechanism targeting the loop region of the LAMP dumbbell structure 28,29 . Our LAMP detection scheme also uses a strand displacement mechanism, but takes advantage of the LAMP reaction’s Bst polymerase to drive strand displacement using the 3’ end of the LAMP product as a primer.…”
Section: Discussionmentioning
confidence: 99%
“…Other systems utilized fluorescently labeled oligonucleotide strand displacement probes that are incorporated into LAMP amplicons ( Bhadra et al, 2015 , 2018 ; Jiang et al, 2017 ; Priye et al, 2017 ). In an RT-LAMP assay for the multiplexed detection of Zika, dengue, and chikungunya viruses in urine samples, probes for each virus were labeled with a different dye to produce a color-coded fluorescent readout ( Yaren et al, 2017 ).…”
Section: Loop-mediated Isothermal Amplificationmentioning
confidence: 99%